Combined Geothermal Heat and Power Plants - Geo-Heat Center (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 2005)
Combined heat and power (CHP) plants are not a new use of energy, whether it be from conventional fossil fuels or geothermal. However, what has been happening recently in the geothermal arena is the use of low-temperature resources (down to 98 C or 208 F) in combination with binary or Organic Rankine Cycle (ORC) power units. Two installations, one in Australia at Birdsville and one in Germany at Neustadt-Glewe, both reported in this issue of the Quarterly Bulletin, are using temperatures this low–the lowest currently operating in the World!! However, there was an even lower temperature use at Paratunka, Kamchatka, Russia; a binary power plant using 81 C or 178 F producing 680 kWe and the wastewater used for heating the soil and water plants in greenhouse, was in operation for a number of years in the late 1960s and early 1970s